Do animal models have a place in the genetic analysis of quantitative human behavioural traits? - Flint, J; Corley, R (1996)
It seems that the genetic basis of common psychiatric diseases such as schizophrenia and manic-depressive psychosis is amenable to the genetic mapping strategies that have been successful in other complex disorders such as diabetes. The next challenge is the genetic dissection of quantitative behavioural traits such as mood, personality and intelligence. Quantitative traits pose new problems for gene cloning experiments. We argue that one way forward is by using animal models. One of the features of quantitative traits is that the DNA sequence variants which are responsible for them are unlikely to be immediately recognizable. In contrast to many qualitative traits where a discrete phenotypic difference is often the consequence of an inactivating mutation, the allelic variation responsible for quantitative traits probably has a more subtle basis. This distinction means that strategies to clone the genetic basis of quantitative behavioural traits will have to rely on functional assays of alleles thought to be important in determining the phenotype. We suggest that an efficient strategy for detecting sequences that give rise to quantitative behavioural traits can be devised in the mouse. The importance and utility of the mouse for quantitative trait analysis make it worthwhile to investigate mouse models of human behaviour; these advantages outweigh the difficulties that arise in attempts to validate the animal models. As an example we review the evidence that validates rodent emotionality as an animal model for susceptibility to human anxiety. We show that there is good evidence that rodent emotionality is a central nervous system state with a genetic basis, and that there are neuropharmacological and neuroanatomical parallels with human anxiety. Furthermore, our own work has shown that the genetic basis of the trait is relatively simple, and that the task of characterizing it at a molecular level is feasible. We expect that future experiments will show us how genetic variation gives rise to quantitative behavioural traits.